Hydrothermal Synthesis and Acetylene Sensing Properties of Variety Low Dimensional Zinc Oxide Nanostructures - Qu Zhou; Weigen Chen; Shudi Peng; Wen Zeng (The Scientific World Journal)
Various morphologies of low dimensional ZnO nanostructures, including spheres, rods, sheets, and wires, were successfully synthesized using a simple and facile hydrothermal method assisted with different surfactants. Zinc acetate dihydrate was chosen as the precursors of ZnO nanostructures. We found that polyethylene glycol (PEG), polyvinylpyrrolidone (PVP), glycine, and ethylene glycol (EG) play critical roles in the morphologies and microstructures of the synthesized nanostructures, and a series of possible growth processes were discussed in detail. Gas sensors were fabricated using screen-printing technology, and their sensing properties towards acetylene gas (C2H2), one of the most important arc discharge characteristic gases dissolved in oil-filled power equipments, were systematically measured. The ZnO nanowires based sensor exhibits excellent C2H2 sensing behaviors than those of ZnO nanosheets, nanorods, and nanospheres, indicating a feasible way to develop high-performance C2H2 gas sensor for practical application.